HEAVY METALS POLLUTION INDICES IN TANNERY SLUDGE FERTILIZED FARMS AROUND HAUSAWAN KABA, KANO, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
with the highest contamination factor was Cadmium (Cf = 8.51) in Farm 2 while Iron had the lowest with about 0.001 in Farm 3. Cadmium had the highest enrichment factor value in Farm 2 (Ef =  4634.92) while Fe had the lowest Ef of 1.00 in all farms. The lowest geoaccumulation index (Igeo) was – 8.77 for Pb in Farm 2 while the highest was 15.39 for Cadmium in Farm 3. Igeo >5 showed that all the farms are extremely polluted with heavy metals.  Pollution load index (PLI) occurred in the order: Farm 3 (0.43) < Farm 2 (0.88) < A study was conducted to assess the influence of tannery sludge on heavy metals pollution indices in Hausawan Kaba, Kano, Nigeria. Three farms were randomly selected as sampling stations and named farm 1, farm 2 and farm 3. Soil samples were collected using soil auger, digested using concentrated HCl and analysed using Flame Atomic Absorption Spectrophotometer (FAAS). The highest metal concentration was Pb in Farm 2 with an average value of 130.62 ± 61.12 mg/kg while the lowest was Cadmium in Farm 3 with a concentration of 1.33 ± 2.17 mg/kg.  All metal concentrations differed significantly across farms at 0.05 level of significance and they have exceeded World Health Organization (WHO) 1996 maximum permissible limits. The metal Farm 1 (1.13).
Keywords: Flame Atomic Absorption Spectroscopy, Pollution index, Contamination factor, Enrichment factor, Geoaccumulation index, Pollution load index